2011
DOI: 10.1093/ndt/gfr569
|View full text |Cite
|
Sign up to set email alerts
|

Urine neutrophil gelatinase-associated lipocalin identifies unilateral and bilateral urinary tract obstruction

Abstract: uNGAL identifies kidney injury in unilateral and bilateral UTO even in the absence of an elevated sCr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…However, our analysis shows that there are minimal differences in the predictive accuracy of uNGAL for UTI when patients with augmented bladders are included and excluded for the cohort, suggesting that the gastrointestinal epithelium is not a large contributor of uNGAL in this clinical setting. Other potential confounders include the possibility of obstruction, as uNGAL concentrations are elevated in the setting of acute urinary tract obstruction [27]. However, the increase in uNGAL concentrations in acute obstruction is likely due to acute kidney injury, which is not present in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis shows that there are minimal differences in the predictive accuracy of uNGAL for UTI when patients with augmented bladders are included and excluded for the cohort, suggesting that the gastrointestinal epithelium is not a large contributor of uNGAL in this clinical setting. Other potential confounders include the possibility of obstruction, as uNGAL concentrations are elevated in the setting of acute urinary tract obstruction [27]. However, the increase in uNGAL concentrations in acute obstruction is likely due to acute kidney injury, which is not present in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression analysis has shown differences in the genes expressed in acute kidney injury due to different processes, even if the magnitude of rise in creatinine is the same. Conversely, serum creatinine concentration can be normal with documented tubular injury due to the delayed achievement of detectable changes of this analyte (74). Generally, hemodynamically driven increases in serum creatinine resolve with treatment in 24 to 72 h, whereas the cellular derangements due to acute tubular damage, or even necrosis, may last for weeks (75).…”
Section: Knowledge Gaps In the Use Of Extracorporeal Uf In Heart Failurementioning
confidence: 99%
“…A systematic study of thousands of genes encoding for several biomarkers including NGAL, kidney injury molecule-1, tissue inhibitor of metalloproteinase-1, and clusterin, found that these molecules were detectable after a brief dose of ischemia, yet none of these genes were expressed after near-fatal volume depletion, despite the rise in serum creatinine in both models (80). Although this method is not yet widely available, in the setting of any method of fluid removal, the levels of urine NGAL and other biomarkers of tubular injury could potentially help distinguish a rise in serum creatinine due to a hemodynamically mediated decrease in glomerular filtration rate or actual tubular injury (74). Numerous genes are differentially expressed depending upon the presence and type of acute kidney injury.…”
Section: Knowledge Gaps In the Use Of Extracorporeal Uf In Heart Failurementioning
confidence: 99%
“…As NGAL is a marker of tubular injury, it may have clinical use as a marker of renal damage due to a variety of obstructive conditions. Early work in adults suggests that uNGAL is superior to serum creatinine in identifying both bilateral and unilateral obstruction [21]. Subsequently, in children, uNGAL has shown promise as a marker of ureteropelvic junction obstruction [22], and in patients with renal dysfunction due to hydronephrosis [23].…”
Section: Ngal and Urinary Tract Obstructionmentioning
confidence: 99%